1991
DOI: 10.1055/s-2007-1014424
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Versus Placebo: A Double-Blind Study with Bulimic Inpatients Undergoing Intensive Psychotherapy

Abstract: In a double-blind trial 40 patients with bulimia nervosa according to DSM III-R criteria were randomly assigned either to a 60 mg fluoxetine group or to a placebo control group. Fluoxetine or placebo was given over a period of 35 days. Parallel to the drug trial, patients participated in an intensive inpatient behavioral psychotherapy program. There were no dropouts at all in the study. Fluoxetine was well tolerated and had only minor adverse effects. In self-ratings and expert ratings concerning attitudes tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
3

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 4 publications
(4 reference statements)
1
46
0
3
Order By: Relevance
“…[3][4][5] Various classes of antidepressants have been used, including tricyclic antidepressants, monoamine oxidase inhibitors and more recently serotonin reuptake inhibitors. [6][7][8][9][10][11][12] Although agents from all of these classes have been shown to be effective, given their side effects profile, the serotonin reuptake inhibitors appear to be the drugs of choice, and fluoxetine remains the only FDA approved medication for bulimia nervosa. 10 One small randomized trial also suggests efficacy for sertraline.…”
Section: Psychopharmacological Of Bulimia Nervosamentioning
confidence: 99%
“…[3][4][5] Various classes of antidepressants have been used, including tricyclic antidepressants, monoamine oxidase inhibitors and more recently serotonin reuptake inhibitors. [6][7][8][9][10][11][12] Although agents from all of these classes have been shown to be effective, given their side effects profile, the serotonin reuptake inhibitors appear to be the drugs of choice, and fluoxetine remains the only FDA approved medication for bulimia nervosa. 10 One small randomized trial also suggests efficacy for sertraline.…”
Section: Psychopharmacological Of Bulimia Nervosamentioning
confidence: 99%
“…The results of some studies examining these issues indicate that cognitive-behavioral therapy alone is generally superior to a trial of a single antidepressant agent and suggest that there may be some advantage to combining cognitive-behavioral therapy with antidepressant medication (9,(11)(12)(13). However, several important clinical questions were not completely resolved by the available data.…”
mentioning
confidence: 99%
“…In contrast to this however Agras et al [1992] carried out a controlled evaluation of desipramine and cognitive-behavioural therapy and found that combination therapy for 24 weeks showed a significantly greater sustained response than medication alone for 16 weeks, and concluded that, in their hands, a combination of psychotherapy and pharmacotherapy is most effective. Finally, a study by Fichter et al [1991] comparing fluoxetine with placebo in patients undergoing 'intensive psychotherapy', also demonstrated a 'celling effect'. Further studies may be useful to further clarify the relative efficacies of pharmacotherapy and psychotherapy, and the presence or absence of any additive effects.…”
Section: Drugs Versus Psychotherapymentioning
confidence: 96%
“…Another potential advantage of fluoxetine is that there is some evidence that patients are likely to lose weight or stay at the same weight whilst taking it [Solyom et al, 1990;Fichter et al, 1991], and this makes it a far more attractive proposition to many women with BN. For tricyclic antidepressants there is most evidence for the efficacy of desipramine in a dosage of 200-300 mg/day, and there is a third choice in the monoamine oxidase inhibitors, although these groups of drugs probably have little or no place in the treatment of BN not complicated by depressive illness.…”
Section: Selecting Patients For Drug Treatmentmentioning
confidence: 99%